Incentives, Globalization, and Redistribution - Andreas Haufler; Carlo Perroni (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We offer a new explanation for why taxes have become less progressive in many countries in parallel with an increase in income inequality. When performance-based compensation differentials are needed to incentivize effort, redistribution through progressive income taxes becomes less precisely targeted. Taxation reduces after-tax income inequality but undermines incentive contracts, lowering effort and raising pre-tax income differentials. Market integration can widen the spread of project returns and make contract choices more responsive to changes in the level of taxation, resulting in a lower optimum income tax rate even when individuals are not inter-jurisdictionally mobile.
Keywords: H21; F15; D63; 330; redistributive taxation; performance-based contracts; market integration